2012
DOI: 10.2514/1.j051074
|View full text |Cite
|
Sign up to set email alerts
|

Use of Blowing Flow Control to Reduce Bluff Body Interaction Noise

Abstract: When an unsteady wake from an upstream body impinges on a downstream body, the resultant interaction noise can be significant. The use of distributed blowing through the surface of a cylinder to reduce this source of noise was investigated in a series of experiments. The two bluff bodies in tandem were a cylinder and an H-beam. Two configurations were tested, one with the cylinder upstream of the H-beam (OH configuration) and the other with the H-beam upstream of the cylinder (HO configuration). The default se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
(20 reference statements)
1
12
0
1
Order By: Relevance
“…Note that the f 1 -tone in the case of LB131 protrudes by approximately 23 dB above the broadband energy content, while this protrusion is of the order of 10 dB for LB41. It is observed that beyond St ≈ 2, specifically within St ≈ 7-9, broadband peaks are evident for all LB cases, which can potentially be attributed to the blowing self-noise phenomenon, as documented by Angland et al (2012). It is difficult to determine which part of the blowing system (i.e.…”
Section: Far-field Noise Spectramentioning
confidence: 97%
See 2 more Smart Citations
“…Note that the f 1 -tone in the case of LB131 protrudes by approximately 23 dB above the broadband energy content, while this protrusion is of the order of 10 dB for LB41. It is observed that beyond St ≈ 2, specifically within St ≈ 7-9, broadband peaks are evident for all LB cases, which can potentially be attributed to the blowing self-noise phenomenon, as documented by Angland et al (2012). It is difficult to determine which part of the blowing system (i.e.…”
Section: Far-field Noise Spectramentioning
confidence: 97%
“…An extension tube of 2 m was connected to the microphone-holder brass tube to eliminate the spurious tones related to the standing waves in the flexible tubing. Panasonic WM-61A microphones have been used by many (Angland et al 2012;Maryami et al 2019Maryami et al , 2020Vemuri et al 2020;Maryami et al 2022aMaryami et al , 2023c to produce reliable pressure data over the frequency range of interest (20 Hz ≤ f ≤ 10 kHz).…”
Section: Chamber Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the key to reducing the interaction noise is to reduce both convection velocity and turbulent stress in the wake flow that impinges on downstream components. [13] In this study, a plane jet is proposed to reduce the flowinduced noise. Tandem rods were used as the test body because turbulent wake from upstream rods can cause more noise emission when it impinges on the rear rod.…”
Section: Introductionmentioning
confidence: 99%
“…钝体绕流是生活中常见的流动形式之一,流体从钝体表面分离、失稳产生 非定常的涡脱落,并向外辐射噪声 [1] 。钝体绕流辐射噪声是典型的流-固-声耦合 问题,广泛存在于工程应用之中,如飞机起落架,潜艇围壳以及高速列车等方 面。Inoue 等 [1] 将圆柱绕流发声机理解释为:当尾涡从圆柱表面脱落时,会诱导 产生沿表面外法线方向的压力脉冲,并以偶极子类型向外辐射噪声。钟思阳和 黄迅 [2] 以平板前缘和后缘为例,解释了结构表面脉动压力辐射噪声的机理。上 述研究表明尾涡脱落对圆柱辐射噪声具有重要影响。因此可以通过控制尾涡脱 落来改变圆柱的流体动力,从而调制辐射噪声。 主动流动控制通过对流场施加小扰动来调制流动结构,在增升 [3] 、减阻 [4] 和 抑振 [5] 等方面取得了显著效果。王成磊等研究了前吸后吹控制对涡激振动圆柱 [5] 、 合成射流控制对涡激振动圆柱 [6][7] 以及合成射流控制对固定圆柱 [8] 流场的影响。 通过数值模拟证明了对固定圆柱施加开环合成射流控制后,存在频率锁定的情 况,并结合线性稳定性分析,确定了发生频率锁定的控制参数的理论变化范围 [8] 。除此以外,利用深度强化学习还能实现更为复杂的控制目标 [4] [9][10] 。主动流 动控制对流场的影响已经成为近些年来研究的热点,而主动流动控制对声场的 影响也吸引了流致噪声领域研究者的不断关注 [11][12][13][14][15][16][17][18][19][20][21] 。Du 等 [11] 利用闭环旋转控制, 从涡和声两个角度出发,得到了展向涡量与升力系数及声压之间的线性关系, 实现了最大 10dB 的降噪效果。黄迅等 [12] 在圆柱表面设置等离子射流装置,在 雷诺数为 2.1×10 5 条件下将远场范围的噪声降低了 3dB。Ma 等 [13][14] 研究了强迫 振动控制对圆柱噪声辐射的影响,将控制频率对声压的影响规律分为三种情况, 并给出了相应的经验公式。Guo [15] 认为流固耦合是非线性的过程,但声传播是 线性的,基于声场的线性叠加原理,提出了一种利用相位相消实现低噪声辐射 的射流控制方法。 在圆柱上施加合成射流控制时,射流孔处周期性的瞬时质量变化相当于在 流场中引入了单极子声源 [16] ,同时由于射流孔处的动量也在周期性变化,还会 在圆柱表面产生偶极子声源。Inoue 等 [16] 利用强度较小的吹/吸控制进行研究, 施加控制之后圆柱流场几乎不发生变化,也避免了频率锁定情况的出现。结合 数值模拟的结果并从声源线性叠加的角度出发,解释了吹/吸控制产生的单极子 和圆柱表面流体动力脉动产生的偶极子之间相互作用对声场的影响机理。但在 减阻过程中,合成射流控制不仅会引入额外的噪声,还会对圆柱尾涡脱落产生 影响,造成圆柱表面流体动力的变化,导致流体动力产生的偶极子发生改变, 并最终改变远场的辐射噪声。因此,需要进一步研究不同频率和相位差的合成 射流控制对圆柱绕流声场的影响。 数值模拟是研究流噪声的有效途径。根据是否需要求解声比拟方程,可以 将流噪声数值模拟方法分为直接方法和混合方法 [22] 。直接方法是通过求解可压 缩流动控制方程组获得流场中的压力。混合方法则是将流场与声场解耦,将流 场计算结果作为输入求解声场。三维情况下,声波以脉冲形式向空间中传播, 通过直接方法与混合方法求解得到的声场符合良好。但在研究二维问题时,除 了声源发出的声压脉冲之外还包含尾波 [23] ,需要将之前时刻的影响全部叠加起 来,在三维条件下推导的声比拟方程的解不再适用。Guo [23] 通过更换格林函数, 获得了 Ffowcs Williams/Hawkings 方程的二维频域解。类似地,Inoue 等…”
unclassified